2015
DOI: 10.7314/apjcp.2015.16.3.979
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Awareness about Breast Cancer and its Early Symptoms among Medical and Non-Medical Students of Southern Punjab, Pakistan

Abstract: Breast cancer is the leading cause of morbidity and mortality globally but has an even more significant impact in developing countries. Pakistan has the highest prevalence among Asian countries. A general lack of public awareness regarding the disease often results in late diagnosis and poor treatment outcomes. The literacy rate of the Southern Punjab (Pakistan) is low compared to its Northern part. It is therefore vital that university students and especially medical students develop a sound knowledge about t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
34
4
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 14 publications
5
34
4
1
Order By: Relevance
“…Fortunately, the bulk of the students in our study (76.1%, n=290) identified lump and nipple discharge 59.6% (n=227 as important symptom of Breast cancer Tis is higher than a local study which has reported an overall inadequate knowledge of sign symptoms of breast cancer where only 37.4% identified lump and 21% mention pain as chief symptoms of disease [20]. In our study also it was noticed that 64% (n=244) respondents have misconception that pain is an important symptom of breast cancer but a study in Punjab showed better understanding of respondents regarding pain that it does not always indicate breast cancer [21]. Similarly a survey conducted in Angola also showed deficient knowledge among university students about early sign of BC and recommended educational programs to increase the awareness to encourage screening and early detection [14].…”
Section: Reasonscontrasting
confidence: 52%
See 2 more Smart Citations
“…Fortunately, the bulk of the students in our study (76.1%, n=290) identified lump and nipple discharge 59.6% (n=227 as important symptom of Breast cancer Tis is higher than a local study which has reported an overall inadequate knowledge of sign symptoms of breast cancer where only 37.4% identified lump and 21% mention pain as chief symptoms of disease [20]. In our study also it was noticed that 64% (n=244) respondents have misconception that pain is an important symptom of breast cancer but a study in Punjab showed better understanding of respondents regarding pain that it does not always indicate breast cancer [21]. Similarly a survey conducted in Angola also showed deficient knowledge among university students about early sign of BC and recommended educational programs to increase the awareness to encourage screening and early detection [14].…”
Section: Reasonscontrasting
confidence: 52%
“…Similar result was reported in another Pakistani research [20] conducted on 1304 females of 18 years and above in Karachi and Islamabad which has reported that 60.3% considered it as a major health problem. However, another study conducted in Punjab on medical and non-medical students showed that 73% nonmedical and 80% medical students knew that BC is the most prevalent cancer among Pakistani women [21].…”
Section: Reasonsmentioning
confidence: 96%
See 1 more Smart Citation
“…Early warning signs and regular screenings of breast can help in early detection and treatment of disease. 10 A family history of breast cancer, and genetic mutations are seen to be the main factors which amplify the risk of development of breast cancer in women 7 although risk factors for developing this disease may be genetic, hormonal, sociobiological, physiological, environmental, high cholesterol diet, obesity, lifestyle, early menarche, late menopause, nulliparity, late first child and no breastfeeding. 2,5,11 Women living in developing countries like Pakistan have scarce knowledge about breast cancer and its screening methods hence the purpose of our study was to know the level of information about the disease, so that different measures could be taken to enhance the knowledge and prevent the mortalities and morbidities.…”
Section: Introductionmentioning
confidence: 99%
“…A recent report from Shaukat Khanum Memorial Cancer Hospital and Research Center (SKMCH & RC) in Lahore, Pakistan shows 45.9% of malignancies to be breast cancer among adult females from December 1995 to December 2009 [8]. Breast cancer statistics in Pakistan have not been exact or adequate due to the absence of a cancer registration system at national level [8,9]. …”
Section: Introductionmentioning
confidence: 99%